Correlation between TG/HDL-C ratio and obstructive sleep apnea in the adult US population: a cross-sectional study - Yang, Yanlin; Wu, Gaohui; Ren, Lingyun (Frontiers in Neurology, 2025)
BackgroundObstructive sleep apnea (OSA) is associated with dyslipidemia, neurocognitive impairment, and cardiovascular morbidity. This study investigates the triglyceride-to-high-density lipoprotein cholesterol ratio (TG/HDL-C) as a composite biomarker for OSA prevalence, with implications for mitigating OSA-associated complications through metabolic modulation.MethodsA nationally representative cohort of 3,270 adults (NHANES 2015–2018) was analyzed using weighted multivariate logistic regression. Restricted cubic splines (RCS) modeled nonlinear associations, while receiver operating characteristic (ROC) curves evaluated predictive performance against conventional lipid indices (TG, HDL-C) and composite lipid indices (TG/HDL-C, NHHR). The DeLong test further compares the predictive efficacy between models. The differences between groups in predicting OSA based on TG/HDL-C levels were further examined via subgroup analysis.ResultsSignificant differences in lipid profiles were observed between OSA and non-OSA cohorts (p < 0.001). Each unit increase in TG/HDL-C conferred a 17% elevated OSA risk [OR = 1.17; 95% CI: 1.00–1.35; p = 0.045], with a nonlinear dose–response relationship (p for interaction = 0.017). TG/HDL-C demonstrated superior predictive accuracy (AUC = 0.589) versus NHHR (AUC = 0.572). Subgroup analyses indicated that TG/HDL-C as an indicator of OSA varied by the family income to poverty ratio (PIR) group, as well as among congestive heart failure and angina populations (p for interaction < 0.05).ConclusionThis study demonstrates that the TG/HDL-C ratio is a superior predictor of OSA risk compared to TG and NHHR. These findings underscore the clinical utility of composite lipid indices TG/HDL-C for early OSA detection and targeted intervention.